Development of quality control parameters for two Bhutanese medicinal plants (Aster flaccidus Bunge and Aster diplostephioides (DC.) Benth. ex C.B.Clarke) using traditional and modern pharmacognostical platforms - Ngawang Gempo; Karma Yeshi; Tenzin Jamtsho; Lungten Jamtsho; Samten; Phurpa Wangchuk (Heliyon, 2024)
Bhutan's scholarly traditional medical system is called Bhutanese Sowa Rigpa medicine (BSM). It was integrated with the modern healthcare system in 1967. Over 200 medicinal plants are used to produce more than 100 poly-ingredient medicinal formulations. Although BSM is supported by well-documented principles, pharmacopoeias, diagnostic procedures, treatment regimens, and traditional quality assurance systems, modern quality control parameters have become essential to distinguish closely related species and prevent contamination from exogenous impurities. This study aims to establish reliable analytical methods and quality control parameters for Aster flaccidus Bunge and Aster diplostephioides (DC.) Benth. ex C.B. Clarke used as ingredients in the BMS poly-ingredient medicinal formulations. Furthermore, their reported phytochemicals and biological activities are also discussed in this study. Standard pharmacognostic techniques, including macroscopical and microscopical examinations of crude drugs, were employed to establish the quality control parameters for two Aster species. The physicochemical limits were determined as per the World Health Organization (WHO)-recommended guidelines and methods described in the Thai herbal pharmacopoeia. A high-performance thin-layer liquid chromatography (HPTLC) was used to develop a comparative chromatogram/phytochemical fingerprint for the crude extracts obtained from two Aster species. A literature review was conducted to record their isolated phytochemicals and biological activities. Two Aster species possess macro- and microscopic features such as colour, appearance, and shape. Physicochemical analysis of crude drugs from two Aster species including HPTLC fingerprinting of their methanol crude extracts also yielded adequate data to differentiate and confirm two Aster species before adding them to the BSM poly-ingredient medicinal formulations. From the literature review, only A. flaccidus was found to be studied for its phytochemical constituents, whereby 11 pure compounds were isolated from aerial parts and roots. The current study revealed distinct species-specific distinguishing features, including ecological adaptation, micromorphology, anatomy, physicochemical values, HPTLC chromatograms. These parameters can be used to authenticate the species identity and prevent adulterations, thereby improving the quality and safety of BSM formulations.